The role of language environment in the quality and development of spoken English among ESL Children - Rahim, Zurahani (2018)
Oral language production or speaking among learners of English as a Second Language (ESL) is relatively less explored than other skills such as reading and writing. Speaking has been found to be the weakest skill among all major proficiency skills for ESL learners and teachers alike as in the case of Malaysia (English Language Standards & Quality Council, 2015). Recognising the gaps in research, there is a need to better explain the nature of ESL learners, and how language learning environment affects the development of spoken language. Studies exploring characteristic features of ESL learners i.e. age of acquisition (AoA), the interaction between first and second/other languages and language distance, and a range of environmental and/or exposure factors that influence the way in which spoken English is developed within and beyond the ESL language classroom are reviewed and discussed. Preliminary results highlight emerging themes for consideration to facilitate in the development of oral language proficiency and spoken English among young ESL speakers. Quality, quantity, frequency, density, and intensity of language exposure were of particular importance. The study re-evaluates the significance and conduciveness of language learning and exposure environments, highlighting the necessary and impactful elements alongside pedagogical concerns. Possible avenues for future research in the optimal development of spoken English among ESL learners in a non-native English speaking environment are discussed.